If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2x = 3x + 2 Combine like terms: 9x + -2x = 7x 7x = 3x + 2 Reorder the terms: 7x = 2 + 3x Solving 7x = 2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7x + -3x = 2 + 3x + -3x Combine like terms: 7x + -3x = 4x 4x = 2 + 3x + -3x Combine like terms: 3x + -3x = 0 4x = 2 + 0 4x = 2 Divide each side by '4'. x = 0.5 Simplifying x = 0.5
| 6.25=w/5 | | 3x+5=2(2x-1)+x-3 | | 2w+18=74 | | u/806=558/468 | | -6=2(x-4)-2x | | 7/8x-5/16 | | -6=2(x)-2x | | 2w= | | 1/4(a-8)=5a | | y-7y-6=30 | | 0=-16t^2-32t-277 | | 3x-8=6x+2 | | 9y-8y-49y+6*6*6= | | .14y+4=2 | | 5x+2-1x=-4x | | 5/16y=5/6 | | (x+10)+(x-14)= | | 4x/10=150 | | 1/2(x-2)=27 | | 3x-y=125 | | T/27=19 | | 7x-4x-36= | | 9-2.4x=-4.5+3x | | 3c+11c-17c= | | Ln(5x)+ln(x)=7 | | B/6=22 | | x+68=133 | | 2/x=8/20 | | y=-5+8x | | (7/6)k=(7/18) | | 2(1x-5)=4x-2(1x+5)+1 | | 13y-95=6y |